Penguatan Administrasi Faktur Obat di Rumah Sakit melalui Keterlibatan Mahasiswa Magang - Fida Kurnia Widiyanti; Citra Lutfia (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
Drug invoice The management of pharmaceutical invoices is a crucial aspect of hospital administration, supporting organized documentation, administrative control, and financial management. However, implementation often faces challenges such as unsystematic document archiving, inconsistent data recording, and the absence of a standardized data backup format. This activity aims to describe the contribution of interns to strengthening pharmaceutical invoice administration at the hospital. A participatory approach utilizing qualitative descriptive methods was employed. Interns were directly involved in data entry, validation, archiving, creating data backups, and monitoring the management of invoices from pharmaceutical wholesalers. Data were gathered through participant observation, semi-structured interviews, and document review, then analyzed descriptively by comparing administrative conditions before and after the activity. The results indicate that intern involvement contributed to more systematic invoice organization, the implementation of data validation prior to transaction closing, the establishment of a standardized data backup format, and easier document retrieval. These improvements enhanced administrative quality and the reliability of the hospital's financial administration. Furthermore, utilizing Microsoft Excel for data storage fostered administrative orderliness and facilitated document verification, transaction tracking, and financial reconciliation. These findings demonstrate that intern involvement positively impacts the effectiveness of pharmaceutical invoice administration at the hospital. Thus, structured pharmaceutical invoice management serves as a means to support more organized, effective, and accountable hospital administrative governance and financial management.